Nilai Ekologis dan Etika Agraris dalam Naskah Wulang Tani: Kajian Ekolinguistik - Mahanani, Endah Normawati; Setyanto, Suroto Rosyd; Lestari, Endang (Jurnal Pendidikan Bahasa dan Sastra Indonesia Metalingua, 2025)
The purpose of this study is to identify and analyze the forms of ecological value representation in the Wulang Tani manuscript through an ecolinguistic approach and to describe the agrarian ethical system embodied in traditional Javanese agricultural discourse as recorded in the Wulang Tani manuscript. The source of this research data is the Wulang Tani manuscript that has been translated, while the data are lexicons, phrases, clauses or sentences that represent ecological values and agrarian ethics in the Wulang Tani manuscript. The method used in this study is descriptive qualitative. The data collection technique uses literature studies and the analysis technique uses a descriptive qualitative method with an ecolinguistic approach. The results of this study are representations of lexicon values that are seen in the selection of lexicons related to plant types, agricultural terms, types of pests, agricultural guidelines, and climate and geographical awareness. In addition, this study also focuses on agrarian ethics that are explicitly and implicitly stated in the Wulang Tani manuscript. Agrarian ethics in the Wulang Tani manuscript include: honesty and a peaceful life, patience and perseverance, simplicity and non-greed living, and mutual cooperation and generosity.Keywords: Ecological Values, Agrarian Ethics, Wulang Tani, Ecolinguistics